Determinants of Team Performance in Hospitality Team Learning: A Case Study at a Polytechnic in Hangzhou - Li, Qingsu (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: The purpose of this study is to explore the factors influencing team performance in team-based learning within a hospitality program at a polytechnic in Hangzhou, China. Research design, data and methodology: A mixed methods design was adopted. Quantitative data were collected through surveys from 80 students and analyzed using multiple linear regression (MLR) to test the conceptual framework. A 12-week Intervention Design Implementation (IDI) was then carried out with a group of 30 students. Pre- and post-intervention surveys were compared using paired-sample t-tests. Qualitative interviews with students and teachers supported the intervention design and provided contextual understanding. Results: MLR analysis indicated that knowledge sharing (β = 0.345, p = 0.027) and team cohesion (β = 0.622, p < 0.01) significantly influenced team performance (R² = 0.783), while coordination and collective efficacy were not statistically significant. However, paired-sample t-tests showed significant improvements in all four factors after the intervention: coordination (p = 0.013), knowledge sharing (p = 0.002), collective efficacy (p = 0.001), and team cohesion (p < 0.001), along with team performance overall (p = 0.001). Conclusions: The findings highlight that while some factors initially show stronger influence, all targeted team competencies can be improved through structured interventions of supporting more effective team-based learning in hospitality vocational education.